Psychological health conditions of ART treated infertile couples: a 4-years prospective study - Cattaneo Della Volta, Maria Francesca; Vallone, Federica; Dolce, Pasquale; Zurlo, Maria Clelia (Frontiers in Psychology, 2025)
IntroductionInfertility literature has well-demonstrated the psychological burden of long-term Assisted Reproductive Technologies treatments and repeated failures, but there is a lack of studies following couples over time, starting from the beginning of the infertility/treatment path, so allowing a greater understanding of the potential outcomes couples may go through (Parenthood after Successful Treatments, PST; Parenthood by Adoption, PA; Childless still Pursuing Treatments, CPT; Childless Quitting Treatments, CQT) and, accordingly, exploring the different impact on their psychological health. This prospective study aims at assessing and comparing psychological health reported by male and female partners of infertile couples at two-time points (T1-beginning of medical treatments; T2-after 4 years), grouping them by the outcome.MethodsParticipants were 108 couples out of 115 couples undergoing infertility treatments recruited in 2018 (T1) available for the follow-up and grouped by the outcome in 2022 (T2). Psychopathological symptoms, measured by SCL-90-R, were assessed at T1 and T2 and compared by outcome groups and sex. Linear Mixed Effect Models were used. Frequencies/percentages of clinically relevant levels of psychopathological symptoms were also explored.ResultsStatistically significant Group-by-Time interaction effects were found. At T1, members of infertile couples reported a substantially comparable psychological portrait, while significant changes at T2 according to the prospective outcome groups for all SCL-90-R subscales were found. Some specificities in changes by sex also emerged. Overall, findings showed a significant increase in psychopathological symptoms among both members of couples Childless and Pursuing Treatments (CPT) and a decreasing trend among members of couples who achieved Parenthood after Successful Treatments (PST) or by Adoption (PA), mainly among men. Considering clinically relevant psychopathological symptoms, data confirmed the abovementioned trends, yet further sex specificities in clinical profiles were found. At T2, CPT couples showed noteworthy increases in clinical obsessive-compulsive symptoms (among women), hostility and interpersonal sensitivity (among men), and anxiety, depression, and paranoid ideation (across sex). Differently, somatization increased over time in women of all prospective outcome groups.DiscussionFindings can be used to develop tailored evidence-based interventions to promote psychological health and prevent disease escalation during/after infertility treatments.